Smashing the racket. Issue 3 (June 2016) - Paulden, Tim
Abstract : Are some professional tennis players really taking "backhanders" to throw matches? Tim Paulden explains how spotting anomalous movements in the betting markets can help shine a light into the murky world of tennis match‐fixing Abstract : Are some professional tennis players really taking "backhanders" to throw matches?Tim Paulden explains how spotting anomalous movements in the betting markets can help shine a light into the murky world of tennis match‐fixing